Odpowiedź :
[tex]a)\ \ -2(x-1)=x-\frac{1}{4}\\\\L=-2(1,5-1)=-2\cdot0,5=-1\\\\P=1,5-\frac{1}{4}=\frac{15}{10}-\frac{1}{4}=\frac{3}{2}-\frac{1}{4}=\frac{6}{4}-\frac{1}{4}=\frac{5}{4}=1\frac{1}{4}\\\\L\neq P\\\\Liczba\ \ 1,5\ \ nie\ \ spelnia\ \ tego\ \ r\'ownania\\\\\\b)\ \ -x+3=2(\frac{2}{3}-x)\\\\L=-(-1\frac{2}{3})+3=1\frac{2}{3}+3=4\frac{2}{3}\\\\P=2(\frac{2}{3}-(-1\frac{2}{3}))=2(\frac{2}{3}+1\frac{2}{3})=2\cdot1\frac{4}{3}=2\cdot\frac{7}{3}=\frac{14}{3}=4\frac{2}{3}\\\\L=P[/tex]
[tex]Liczba\ \ -1\frac{2}{3}\ \ spelnia\ \ to\ \ r\'ownanie[/tex]